PPLS: An efficient paralle algorithm for Partial Least-Squares - Milidiú, Ruy Luiz; Rentería, Raúl (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2000: Anais do XII Symposium on Computer Architecture and High Performance ComputingDO - 10.5753/sbac-pad.2000.41235, 2000)
PPLS, a parallel version for the Partial Least-Squares algorithm, is introduced in this article. The proposed algorithm is restricted to the case of only one dependent variable for the regression model. Unlike other approaches, such as the ones that calculate the PLS factors through Hebbian learning, PPLS is exact and does not depend on approximation or convergence criteria. In our experiments with a small data set, the algorithm shows a Speedup greater than 3 for the first 4 machines in a computer cluster architecture.